First three physician's assistants complete program at Duke University - American Medical Student Association (American Medical Student Association, 1968)
Article that appeared in the New Physician June 1968: A-18-A-19, describing the first three graduates of the Duke University Physician's Assistant Program. The article describes the curriculum and the backgrounds of the first three graduates: Richard Scheele, Victor Germino and Kenneth Ferrell.